Dispositional Positive and Negative Affect and Self-Employment Transitions: The Mediating Role of Job Satisfaction. (May 2020) - Nikolaev, Boris; Shir, Nadav; Wiklund, Johan
Affect is increasingly studied within entrepreneurship. We develop a partial mediation model in which positive and negative dispositional affect influences entry into entrepreneurship, suggesting that those experiencing greater negative affect experience less job satisfaction and are more likely to enter entrepreneurship. Using a novel methodological approach to capture affective disposition, we test our model on a large panel dataset from Australia, finding support for our hypotheses. These findings provide a much-needed counterbalance to the prevailing focus in entrepreneurship on the positive consequences of positive affect and introduce affect into the study of the fundamental question of why some people but not others become entrepreneurs in the first place.